Digital Marketing Strategy for Enhancing Destination Attractiveness and Tourist Visitation - G. A. Tri Ayu Intan Cahyani; Ni Ketut Kusumaningrum; Dinar Sukma Pramesti (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to analyze the tourism attractiveness of Kelecung Beach, evaluate the implementation of existing digital marketing practices, and develop effective digital marketing strategies to enhance tourist awareness, engagement, and visitation. Method: This study employed a qualitative descriptive-interpretative approach. Data were collected through field observations conducted over a three-month period, semi-structured interviews with 15 key informants consisting of tourism destination managers, local government representatives, tourism business operators, and visitors, as well as document analysis. Data were analyzed using the Miles and Huberman interactive model. Strategic recommendations were formulated through SWOT analysis and mapped using the AISAS (Attention, Interest, Search, Action, Share) framework to identify priority digital marketing strategies. Result: The findings reveal that Kelecung Beach demonstrates strong attractiveness through its natural coastal landscape, tranquil atmosphere, and authentic local tourism experiences. However, digital promotion remains fragmented, with limited social media engagement, inconsistent destination branding, and inadequate online information accessibility. The AISAS analysis indicates that the "Search" and "Share" stages represent the weakest elements in the tourist decision-making process. SWOT analysis further highlights opportunities for digital expansion through content marketing, destination storytelling, influencer partnerships, and integrated social media management. Priority strategies include strengthening destination branding, optimizing official digital platforms, and encouraging user-generated content to improve online visibility and visitor engagement. Contribution: This study contributes to tourism marketing literature by integrating SWOT and AISAS analyses to formulate digital marketing strategies for emerging coastal tourism destinations. The research provides a practical framework for destination branding and digital promotion that can be adapted by similar tourism destinations in Indonesia.